FENOMENA PENGGUNAAN NIQAB OLEH MAHASISWI PERGURUAN TINGGI ISLAM NEGERI DI KOTA KENDARI (STUDI LIVING QUR'AN - Danial Danial (Institut Agama Islam Negeri Kendari, 2019)
This research aims to reveal the students’ understanding about niqab, to scrutinize other university members’ response, students’ who wear niqab resistance at Islamic University in Kendari. This research uses qualitative descriptive method by phenomenon and living Quran approach to know students’ insight of niqob. The data collection uses documentation, interview and observation. Data analysis uses data reduction, validation and taking conclusion using textual and contextual comprehension. The results show that: (1) 80% respondent students of IAIN Kendari who are wearing niqob know the dalil is from Q.S. Al Ahzab : 59 and Q.S. Annur : 31, nevertheless they did not understand the dalil deeply. 2 students consider that it is compulsory, and 8 students consider it as sunnah or optional. (2) university communities’ response to students’ who wear niqob, are first, it is allowed by some requirement; second, it is not permitted if resulting social anxiety, third, the students’ attitude to be more exclusive and introvert; forth, other community feel uncomfortable in communication; and fifth there should be specific regulation for niqob wearer, (3) There are 4 types of students’ resistance, they are, opened resistance (social media exposing), alternative resistance (wearing masker), closed resistance (optional in wearing niqab, partially covered and uncovered), negotiated resistance (negotiating to rector).